PENGARUH PARTISIPASI MASYARAKAT TERHADAP EFEKTIVITAS PEMBANGUNAN PADA DUSUN SARIMADU NEGERI TULEHU - Maya Nova Sari Tuarita; Jean Rosalina Asthenu (Jurnal Administrasi Terapan, 2023)
Based on the results of the study that community participation in the implementation of development in the Tulehu State Sarimadu Hamlet is relatively less visible because some people do not participate in the implementation of the development in the Tulehu State Sarimadu Hamlet, it is relatively low, both in the form of community activity in development implementation, willingness to contribute in the form of thoughts or ideas. , skills, time, energy and responsibility for the success of development. This study aims to determine the level of community participation on the effectiveness of development. The population in this study was the community of Dusun Sarimadu as many as 173 people, the sample in this study amounted to 64 people. Collecting data in this study using observation, interviews and questionnaires (questionnaire). The analytical tool used is simple linear regression analysis. Based on the results of this study, it shows that community participation on the effectiveness of development in Sarimadu Hamlet, Tulehu State has a positive and significant effect. Based on the results of simple linear regression, it is known that the significant value (sig) is 0.000, which means it is less than 0.05. Based on these results, it can be concluded that community participation is very influential on the effectiveness of development, where good participation from the community can help smooth development in Sarimadu Hamlet, Tulehu State. Key words: Society Participation 1; Development Effectiveness 2